Decision tree Penerapan Perhitungan Metode Decision Tree Menggunakan Algoritma Iterative Dichotomiser 3 (ID3) Berbasis Website - Sasmitoh Rahmad Riady; Shita Dwi Ranti; Rila Mandala; Agus Susanto (PUSAT SAINS INDONESIA, 2020)
This study discusses the implementation of the Decision Tree algorithm into a website. Many calculation tools for machine learning methods include Rapidminner, WEKA, etc. These tools can also calculate various other machine learning methods. However, in this tool, many processes are carried out in testing even though only using one method such as the decision tree. Therefore, this study creates a website-based system that focuses on the Decision Tree ID3 method only, The results of the system calculations will be compared with the results of manual calculations. The website-based calculation tool implementation system for the ID3 algorithm is simple and easy to use, only by uploading training and testing data. Then the results of the calculation will be displayed on the website page. Based on the comparison of manual calculations with the system, there is no significant difference from the manual calculations. The system can run online and can access it from anywhere. In addition to displaying the results of calculations, this system also provides a predictive output and rule base from the calculation results of the decision tree algorithm Dipenelitian ini membahas mengenai penererapan perhitungan Decision Tree ID3 kedalam sebuah website, dimana tool perhitungan metode-metode machine learning yang sudah banyak digunakan diantaranya adalah Rapidminner, WEKA dll yang dapat menghitung berbagai metode machine learning lainnya, namun pada tool ini banyak proses dalam melakukan testing walaupun hanya menggunakan satu metode seperti halnya decision tree ID3. Maka dari itu peneliti membuat sebuah sistem berbasis website yang berfocus pada metode Decision Tree ID3 saja, dari hasil perhitungan sistem akan dibandingkan dengan hasil perhitungan manual. Sistem penerpan perhitungan algoritma ID3 berbasis website ini sangat sederhana dan mudah digunakan dalam prosesnya, cukup dengan upload data training dan testing saja maka hasil dari perhitungan akan ditampilkan dihalaman website. Dari hasil perbandingan perhitungan manual dengan sistem, tidak ada perbedaan yang signifikan dengan perhitungan manualnya, dan sistem dapat berjalan dengan online dan di akses dari mana saja, selain menampilkan hasil perhitungan, sistem ini pun memberikan sebuah output hasil prediksi dan rule base dari hasil perhitungan algoritma pohon keputusan.